Dimensi Buta dalam Al-Qur’an: Studi Ayat-Ayat A’mā dengan Aplikasi Metode Tafsir Tematik - Lilik Ummi Kaltsum; Al-Ikhsan Saing (Refleksi: Jurnal Kajian Agama dan Filsafat, 2021)
This article is based on the fact that the Qur’an mentions the meaning of blind in the word a’mā and its derivatives. From the word (lafadz) it has a meaning or a concept and has a broader meaning. What is meant by blind in this research is not just something that cannot be seen in plain view. This means that there is the possibility of other meanings so that it becomes an element of understanding of a particular purpose. So, the main problem that is discussed in this paper is: how is the concept of blind in the perspective of the Qur'an? The results of this study indicate that the Qur’an constructs a system of meaning from the word a’mā (أعمى) and its derivation is born with broader meanings. Blind in al-Qur'an has a lot of attention to people who are considered to be psychologically blind (inward) and as a form of appreciation of the Qur’an, a small portion are mentioned physically blind (outward).